836. PSEUDOTSUGA JAPONICA: Pinaceae. (September 2016) - Ohashi, Hiroyoshi
Summary: Pseudotsuga japonica (Shiras.) Beissn. is described and illustrated. The species is endemic to Japan growing in limited areas in the southern central Honshu and eastern Shikoku. The history of its discovery, and present distribution and ecology are provided.